Concepts about physicians in the Art of Siddha Medicine: A literary review - Divarjitha, T.; Mithursan, T.; Miraaj, R. (University of jaffna, 2025)
Siddha Medicine is one of the oldest traditional systems of medicine among Tamil speaking community. It has grown together with Hindu culture and Tamil civilization since ancient times. Siddha system of medicine is an art which is formed by the combination of ancient cultural & medicinal practices, alchemy and mysticism. Moral disciplines and qualifications of a good siddha physician had been devised by Siddhas sine ancient times. This review was focused to document the concepts regarding physicians mentioned in the ancient siddha literatures. Date for this study were collected from the related siddha text books and research publications on websites. Collected data were subjected to content analysis and humble efforts were made to describe the concepts about physicians clearly. According to the review, various siddha literatures mention the concepts regarding physicians such as their age, names, disciplines, habits, knowledge, skills and responsibilities. Ancient physicians were called as parikaari, Vaithiyan, Maruthuvan, Akathangaaran, Paran and Nanthiyathevan. Elderly age especially between 50-60 years is considered as best to become a physician while younger age is considered as the appropriate age to practice astrology. Physicians should have good appearance, pure thought and action, love, kindness. Patience, humility and generosity towards the patients. They should avoid anger, laziness, fear, boasting, feminism, deception, lying and greed. Physicians should have adequate knowledge and skills about medicines, diseases, astrology and treatment etc. Physicians should protect and take care of their patients. They should treat them equally without any favoritism. They should serve the patients throughout their life at any time until they alive according to Siddha Medicine. Therefore, this review ensures the existence of morals and disciplines among physicians in ancient times. Although some of these ancient concepts regarding physicians are difficult to implement nowadays, most of these concepts are relevant to the current practice of medicine. Good qualities, disciplines, morals and in-depth knowledge of siddha physicians help to establish a good doctor-patient relationship which result in the treatment success and improvement of both the physical and mental health of the patients.
Keywords: Disciplines; Siddha medicine; Physicians; Art